PbrFEN-1 positively regulates pear pollen tube growth and is involved in the self-incompatibility response - Zhi-Heng Sui; Yi-Peng Ye; Ju-Yang Yao; Ya-Ru Wang; Ying Xu; Ce-Xian Cui; Shao-Ling Zhang; Chao Gu (Plant Reproduction, 2026)

Tracing sediment provenance in the eastern Beibu Gulf, South China Sea using detrital zircon U-Pb ages and clay minerals - Yuxin Qin; Xianlong Zhu; Xiaoyan Tang; Heqi Cui; Kaixi Jiang; Ce Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Theoretical investigation on the energetic and exergetic performance improvement method of the high temperature transcritical CO2 heat pump with two-stage expander - Liaoliang Jiang; Tianliang Chang; Shaoqiang Li; Yulong Song; Ce Cui; Feng Cao; Xiaolin Wang (International Journal of Refrigeration, 2026)

The mediator subunit PagMED20 is associated with enhanced vegetative growth and photosynthetic performance in poplar - Xiao Wang; Changwen Xu; Ce Zhang; Xuandong Liu; Binghe Wang; Yanjun Li; Jinxing Lin; Yaning Cui (Journal of Plant Physiology, 2026)

Enhanced photodynamic inactivation against Listeria monocytogenes under blue light mediated by carbon dots derived from ‘Shatian’ pomelo peels for ready-to-eat sausage preservation - Ce Shi; Rui Yang; Xinyu Huang; Ziwei Liang; Layla A. Alahmari; Maha Abdullah Alwaili; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2026)

Enhanced elimination efficiency of rhamnolipid functionalized-nanoliposomes loaded with diacetyl against Listeria monocytogenes biofilms on food-contact surfaces and vegetables - Ce Shi; Yangyang Chen; Xinyu Huang; Ziwei Liang; Tariq Aziz; Shereen Magdy Korany; Fahad Al-Asmari; Amal A. Mohamed; Haiying Cui; Lin Lin (Food Control, 2026)

Three-dimensional reservoir characterization from hard and soft data based on latent diffusion model - Ce Zhang; Gang Liu; Qiyu Chen; Zhesi Cui; Hongfeng Fang; Dajie Chen; Junping Xiong; Kaikai Zhang (Journal of Hydrology, 2026)

Investigation of the interaction between phloretin and Staphylococcus aureus toxin proteins and its application in chicken meat - Hong Li; Ce Shi; Tariq Aziz; Nawal Al-Hoshani; Manal F. Elkhadragy; Abdelrahman R. Ahmed; Haiying Cui; Lin Lin (Food Chemistry, 2026)

Inhibitory mechanism of carvacrol on the early formation of biofilm by Listeria monocytogenes and its application - Haiying Cui; Xingjun Chen; Xiaochen Chen; Ce Shi; Tariq Aziz; Layla A. Alahmari; Ashwag Shami; Lin Lin (Food Bioscience, 2026)

An ejector-enhanced reversible transcritical CO2 system for zero-carbon airports: A 4E assessment based on annual dynamic simulation - Jinzai Yang; Jiajia Guan; Ce Cui; Xiang Yin; Yulong Song; Feng Cao (International Journal of Refrigeration, 2026)

Enhanced eradicative effects of postbiotics derived from Ligilactobacillus salivarius LSA-6 combined with cold plasma against Listeria monocytogenes biofilms for fresh produce preservation - Li Jia; Xinyu Huang; Ziwei Liang; Tariq Aziz; Layla A. Alahmari; Ashwag Shami; Haiying Cui; Ce Shi (Food Bioscience, 2026)

Provenance and sedimentary processes of the Qiongzhou Strait during the Holocene: Evidence from detrital zircon U-Pb geochronology - Xianlong Zhu; Yao Guan; Heqi Cui; Junmin Jia; Ming Su; Yuxin Qin; Ce Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Antifungal efficiency of p-anisaldehyde nanoemulsions against Botrytis cinerea and its application in strawberry preservation - Xinyu Huang; Rongrong Cai; Lijuan Meng; Tariq Aziz; Nada K. Alharbi; Ashwag Shami; Fahad Saad Alhodieb; Saleh A. Alsanie; Mansour Alblaji; Haiying Cui; Ce Shi (Food Bioscience, 2026)

Exploration of the inhibitory and eradicative effects of diacetyl on Listeria monocytogenes biofilms and its potential application on cantaloupe preservation - Ce Shi; Li Jia; Yangyang Chen; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Fakhria A. Al-Joufi; Haiying Cui; Lin Lin (Food Control, 2026)

Experimental exploration and case studies for quantifying soil erosion on subgrade slopes - Jianjie Jiang; Zhen-Dong Cui; Cao Ce (Natural Hazards, 2026)

Provenance of sediments in the Zhongnan Seamount, South China Sea since MIS 3: Insights from clay minerals and geochemical signatures - Letian Zeng; Ce Wang; Ming Su; Heqi Cui (Quaternary Science Reviews, 2025)

Controls on sediment composition of riverine drainage system: insights from geochemical proxies in the Pearl River - Heqi Cui; Ce Wang; Liangjie Wei; Letian Zeng; Junmin Jia; Haiteng Zhuo; Ming Su (CATENA, 2025)

Inversion of on-tree peach firmness via high-fidelity fruit finite element models and sim-to-real deep transfer learning - Jiaqi Xiong; Yilei Hu; Xianbin Gu; Ce Yang; Di Cui (Biosystems Engineering, 2025)

Exploring the anti-Listeria monocytogenes mechanisms of the postbiotics derived from Ligilactobacillus salivarius LSA-6 and its biopreservative effects on Inner Mongolian cheese - Ce Shi; Li Jia; Jinlong Xu; Na Guo; Haiying Cui; Tariq Aziz; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani; Changzhu Li; Lin Lin (Food Bioscience, 2025)

Inactivation mechanisms of carvacrol on Salmonella Typhimurium and its combined inhibitory effects with blue light-405 nm for chicken meat preservation - Haiying Cui; Xingjun Chen; Tariq Aziz; Rania Ali El Hadi Mohamed; Fahad Al-Asmari; Jaza Maqbl Alshammari; Fakhria A. Al-Joufi; Ce Shi; Lin Lin (International Journal of Food Microbiology, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Provenance of sediments in the northern shelf of the South China Sea: Insights from Pb isotopes in detrital K-feldspar - Liangjie Wei; Ce Wang; Heqi Cui; Junmin Jia; Letian Zeng; Ming Su (Marine Geology, 2025)

Antibacterial mechanisms of diacetyl on Listeria monocytogenes and its application in Inner Mongolian cheese preservation via gelatin-based edible films - Haiying Cui; Yangyang Chen; Tariq Aziz; Fahad Al-Asmari; Maher S. Alwethaynani; Ce Shi; Lin Lin (Food Control, 2025)

Mechanism regulation over dual-atom catalyst enables high-performance oxidative alcohol esterification - Ce Liu; Teng Li; Xingchao Dai; Jian Zhao; Liping Zhang; Xinjiang Cui (Science Bulletin, 2025)

Controls on sediment transport from rivers to trenches in passive and active continental margins - Letian Zeng; Ce Wang; David A. Foster; Ming Su; Heqi Cui; Junmin Jia (Science China Earth Sciences, 2024)

Laser Doppler vibrometer enables in-situ monitoring of peach firmness - Dachen Wang; Yilei Hu; Jiaqi Xiong; Yibin Ying; Ce Yang; Di Cui (Biosystems Engineering, 2024)

Regional detrital zircon record of the drainage sediments surrounding the South China Sea: Provenance signature and tectonic implications - Ce Wang; Heqi Cui; Cheng-Shing Chiang; Ming Su; Letian Zeng; Junmin Jia; Liangjie Wei (Earth-Science Reviews, 2024)

Detrital zircons record the provenance and source-to-sink process in the northwestern margin of the South China Sea - Heqi Cui; Ce Wang; Ming Su; Yaping Lei; Letian Zeng; Junmin Jia (Frontiers in Marine Science, 2024)
The northwestern continental margin of the South China Sea, extending from the broad shelf and canyon-growth slope across the Xisha Trough, represents a relic crustal rift that eventually connects to the abyssal plain. However, the provenance and source-to-sink process of sediments in this special topography remains unclear. In this study, we present the detrital zircon U-Pb geochronology of surface sediments from the northwestern margin of the South China Sea to identify the sediment provenance, track the transport pathway, and understand the source-to-sink process in this margin. The results showed that detrital zircons exhibit a wide range of U-Pb ages from 3,062.9 to 41.5 Ma and are characterized by peaks centered on 140–154 Ma, 240–258 Ma, 425–452 Ma, and 738–991 Ma. Statistical analysis indicated that the clastic sediments on the shelf closely resemble those sourced from the Pearl River system. Conversely, sediments on the slope and abyssal plain demonstrated characteristics indicative of multiple sources, primarily originating from the Pearl River, with a minor contribution from the Red River. Further quantitative study revealed a progressive increase (from 8.2% to 43.2%) in the prevalence of Red River-derived sediments with ascending water depth on the shelf and slope, whereas sediment influx in the deepest sector remains predominantly sourced from the Pearl River. This study emphasizes the controls of topography and currents in modulating the transportation of coarse-grained and fine-grained sediments within the source-to-sink system and provides a favorable solution for reconstructing the sedimentary process in continental margins.

Linking Taiwan to the Cathaysia Block during the Cenozoic: Evidence from Pb isotopes in detrital K-feldspar - Ce Wang; Liangjie Wei; Cheng-Shing Chiang; David A. Foster; Heqi Cui; Ming Su (Global and Planetary Change, 2024)

Transcriptome analysis reveals the inhibitory mechanism of phloretin on virulence expression of Staphylococcus aureus and its application in cooked chicken - Hong Li; Changzhu Li; Ce Shi; Manal Y. Sameeh; Fahad Al-Asmari; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Phosphoproteomics analysis reveals the anti-bacterial and anti-virulence mechanism of eugenol against Staphylococcus aureus and its application in meat products - Hong Li; Changzhu Li; Ce Shi; Metab Alharbi; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Energy and economic analysis of a sub-cooler based vapor injection transcritical CO2 heat pump for space heating - Ce Cui; Jiahang Ren; Yulong Song; Xiang Yin; Feng Cao (International Journal of Refrigeration, 2024)

Real-time multi-variable optimization of the interstage subcooling vapor-injection based transcritical CO2 HPWH: An integrated model predictive control approach - Ce Cui; Haowei Xing; Yulong Song; Mirco Rampazzo; Wenyi Wang; Xiang Yin; Feng Cao (International Journal of Refrigeration, 2024)

Inhibitory effects of citral on the production of virulence factors in Staphylococcus aureus and its potential application in meat preservation - Ce Shi; Xu Liu; Yangyang Chen; Jinming Dai; Changzhu Li; Shifa Felemban; Manal M. Khowdiary; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Holocene provenance evolution of the northern South China Sea inferred from detrital zircon U-Pb geochronology and Hf isotopes - Ce Wang; David A. Foster; Ming Su; Yaping Lei; Letian Zeng; Heqi Cui (Global and Planetary Change, 2023)

Triclocarban exposure aggravates dextran sulfate sodium-induced colitis by deteriorating the gut barrier function and microbial community in mice - Mengyu Qin; Hehua Lei; Yuchen Song; Mengjing Wu; Chuan Chen; Zheng Cao; Cui Zhang; Ruichen Du; Ce Zhang; Xian Wang; Limin Zhang (Food and Chemical Toxicology, 2023)

Computer-vision-assisted subzone-level demand-controlled ventilation with fast occupancy adaptation for large open spaces towards balanced IAQ and energy performance - Zhitao Cui; Yongjun Sun; Dian-ce Gao; Jiaxin Ji; Wenke Zou (Building and Environment, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Preparation and characterization of gelatin active packaging film loaded with eugenol nanoparticles and its application in chicken preservation - Lin Lin; Canchao Mei; Ce Shi; Changzhu Li; Mohamed A. Abdel-Samie; Haiying Cui (Food Bioscience, 2023)

Construction of hierarchical carbon fiber Aerogel@Hollow Co9S8 polyhedron for high-performance electromagnetic wave absorption at low-frequency - Ce Cui; Liang Geng; Shan Jiang; Wenhao Bai; Lanling Dai; Shouxiang Jiang; Jian Hu; Erhui Ren; Ronghui Guo (Chemical Engineering Journal, 2023)

Provenance and dispersal patterns of sediments on the continental shelf of northern South China Sea: Evidence from detrital zircon geochronology - Junmin Jia; Ce Wang; Ming Su; Wen Yan; Letian Zeng; Heqi Cui (Marine Geology, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Provenance of sediments in the northern Manila Trench: An assessment from detrital zircon geochronology - Ce Wang; Heqi Cui; Letian Zeng; Ming Su (Science China Earth Sciences, 2023)

Bamboo cellulose–derived activated carbon aerogel with controllable mesoporous structure as an effective adsorbent for tetracycline hydrochloride - Ce Cui; Mengyuan Yang; Jianyu Zhai; Wenhao Bai; Lanling Dai; Li Liu; Shan Jiang; Weijie Wang; Erhui Ren; Cheng Cheng; Ronghui Guo (Environmental Science and Pollution Research, 2022)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

MicroRNA-520c-3p suppresses vascular endothelium dysfunction by targeting RELA and regulating the AKT and NF-κB signaling pathways - Yan Jiao; Dandan Zhao; Fuhua Gao; Xiaoyan Hu; Xinxin Hu; Mei Li; Ying Cui; Xiaoqing Wei; Ce Xie; Ying Zhao; Ying Gao (Journal of Physiology and Biochemistry, 2021)

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

Continental flood basalts of the Huashan Group, northern margin of the Yangtze block – implications for the breakup of Rodinia - Qi Deng; Jian Wang; Zheng-Jiang Wang; Xuan-Ce Wang; Yan-Sheng Qiu; Qing-Xiong Yang; Qiu-Ding Du; Xiao-Zhuang Cui; Xiao-Lin Zhou (International Geology Review, 2013)

Bt rice expressing Cry1Ab does not stimulate an outbreak of its non-target herbivore, Nilaparvata lugens - Yang Chen; Jun-Ce Tian; Wei Wang; Qi Fang; Zunnu Raen Akhtar; Yu-Fa Peng; Hu Cui; Yu-Yuan Guo; Qi-Sheng Song; Gong-Yin Ye (Transgenic Research, 2012)